The Strategic Role of the Nomination and Remuneration Committee in Strengthening Good Corporate Governance: A Systematic Literature Review - Abd. Rasyid Syamsuri; Triska Indah Novianti; Abd. Halim; Afridayanti Surbakti (International Journal of Economic, Business & Applications, 2026)
The Nomination and Remuneration Committee (NRC) is a key mechanism in the implementation of Good Corporate Governance (GCG), ensuring that nomination, evaluation, and remuneration processes for boards of commissioners, directors, and senior management are conducted objectively, transparently, and free from conflicts of interest. This study aims to analyze the strategic role of the NRC in strengthening corporate governance, identify the factors influencing its effectiveness, and examine recent developments in its implementation based on previous research findings. The study employs a Systematic Literature Review (SLR) approach by reviewing scholarly articles indexed in Sinta, Scopus, and Google Scholar published between 2021 and 2026. The selected literature was analyzed thematically to identify patterns, trends, and key findings regarding the role of the NRC in corporate governance practices. The results indicate that the NRC significantly contributes to enhancing transparency in nomination processes, improving the objectivity of remuneration policies, supporting succession planning, and reducing potential conflicts of interest in corporate decision-making. The effectiveness of the NRC is influenced by the independence of committee members, professional competence, regulatory compliance, and the quality of corporate disclosure practices. Furthermore, contemporary governance trends reveal that the NRC’s role has expanded to encompass sustainability issues, Environmental, Social, and Governance (ESG) integration, and the utilization of digital technologies in talent management and performance evaluation. This study concludes that the NRC serves as a strategic governance instrument that supports effective GCG implementation and contributes to improved corporate performance and long-term sustainability.